Towards a Green Metaverse Era. How can experiences during the COVID-19 pandemic trigger law and environmental-related transformations, as well as green data input? - Chrysoula Kapartziani (European Scientific Journal, ESJ, 2024)
In this research paper we explore the impact of digitalization. Specifically, we focus on the intersection of software engineering, sustainability, and accountability. By conducting literature reviews and qualitative research as well, incorporating theories, from scholars like Beck and others about modernity, we address the growing impact of digital systems and AI on environment. As these systems gain importance it becomes crucial to have frameworks in place for holding them accountable in their design and implementation. In today’s era that emphasizes systems without boundaries (as described by Haraway in 2016) it is essential for all stakeholders including software engineers, end users, citizens, governments, and society at large to understand and carefully navigate the consequences of these systems. To achieve a paradigm shift we propose using strategies informed by Science and Technology Studies (STS) in order to understand and shape the socio-technical impact of digital technologies. We argue that accountability should be integrated within sustainability frameworks as an aspect for bringing about transformations. In order to move towards sustainability, it is vital to adopt approaches that effectively comprehend and shape the influence of socio-technical systems within the digital realm. We stress the need for mechanisms that promote accountability towards sustainability as the foundation, for shifts. Our research paper focuses on a variety of studies that explore aspects of software. We examine everything from energy efficiency to the impact that software has on sustainability. We investigate the viewpoints of software professionals on the environmental footprint of digitalization (energy consumption, computer metrics, etc). By using the concept of co production we highlight how technological advancements are closely connected with environmental factors. We emphasize the roles played by governance, knowledge sharing, legal culture improvement and comprehensive education, in shaping our future.